2013
DOI: 10.3855/jidc.2712
|View full text |Cite
|
Sign up to set email alerts
|

Budd-Chiari syndrome due to giant hydatid cyst: a case report and brief literature review

Abstract: Budd-Chiari syndrome is an uncommon disorder characterized by the thrombotic or non-thrombotic obstruction of hepatic venous outflow anywhere along the venous course from the hepatic venules to the junction of the inferior vena cava and the right atrium. The etiology of Budd-Chiari syndrome is classified as primary, attributable to intrinsic intraluminal thrombosis or the development of venous webs; or secondary, caused by intraluminal invasion by a parasite or malignant tumor or extraluminal compression by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Table 1 shows 13 most relevant pathways. The most significant one is related to the coagulation cascades, which is in agreement with the previous reports that Budd–Chiari is a disorder frequently characterized by the thrombotic obstruction of hepatic venous outflow [45,46] . This result indicated that FunMod, relying on the ABC principle (A and C have no direct connection but are connected via shared B intermediates) [47,48] to establish new relationships between proteins from literature co-occurrence, can be effectively used to combine information from the relevant scientific literature and from pathway databases, supporting the discovery of new knowledge.…”
Section: Case Study 1: Analysis Of a Bibliometric Networksupporting
confidence: 91%
“…Table 1 shows 13 most relevant pathways. The most significant one is related to the coagulation cascades, which is in agreement with the previous reports that Budd–Chiari is a disorder frequently characterized by the thrombotic obstruction of hepatic venous outflow [45,46] . This result indicated that FunMod, relying on the ABC principle (A and C have no direct connection but are connected via shared B intermediates) [47,48] to establish new relationships between proteins from literature co-occurrence, can be effectively used to combine information from the relevant scientific literature and from pathway databases, supporting the discovery of new knowledge.…”
Section: Case Study 1: Analysis Of a Bibliometric Networksupporting
confidence: 91%
“…The etiology of primary BCS remains unclear, but the involvement of thrombus, abnormal angioplasty, abnormal blood coagulation, and myeloproliferative disorder has been suggested . The causes of secondary BCS include liver tumors . Hepatocellular carcinoma may develop in advanced cases …”
Section: Guidelines For Diagnosis Of Aberrant Portal Hemodynamicsmentioning
confidence: 99%
“…5, The causes of secondary BCS include liver tumors. [102][103][104] Hepatocellular carcinoma may develop in advanced cases. 5,14…”
Section: Guidelines For Diagnosis Of Bcs Disease Entity and Symptomsmentioning
confidence: 99%
“…Hydatid disease, endemic to the tropics is caused by multiple species of the parasite Echinococcus , most commonly by E. granulosus . 1 Budd-Chiari syndrome is described as extrinsic or intrinsic hepatic venous outflow obstruction at the level of hepatic venules, large hepatic veins, IVC or right atrium. 2 …”
Section: Descriptionmentioning
confidence: 99%